A practical synthesis of 5-functionalized thieno[2, 3-d]pyrimidines. Issue 30 (22nd July 2015) - Wilding, Birgit; Faschauner, Stefan; Klempier, Norbert
Graphical abstract: Abstract: The synthesis of 5-hydroxymethyl-, 5-acetoxymethyl-, 5-formyl- and 5-cyanothieno[2, 3- d ]pyrimidines, the (methyl)-5-carboxylate, and the respective amide functionality was accomplished by building up the functionalized molecule starting from appropriately substituted thiophene precursors. A similar strategy starting from the pyrimidine precursor and subsequent direct functionalization (formylation and cyanation) of the thieno[2, 3- d ]pyrimidine parent compound in position 5 was found to be less feasible.